University Students’ Perspectives in Using Google Classroom for Learning during Covid-19 (Proceedings of English Linguistics and Literature, 2022)
During covid-19 pandemic, online learning has been implemented in various educational institutions. One of the most popular applications used for learning is google classroom. As not many students used this application before, the writers were interested to find out students’ perspectives related to the use of google classroom during the covid-19 pandemic. The writers did a descriptive qualitative research by involving the students from English Language Education Department at Pekalongan University. Interviews were used to collect the data. The research found that most students had positive perspectives about the use of Google classroom. The students acknowledged that the use of Google Classroom eased the learning as well as the submission of assignments. They accepted that Google classroom was easily accessed and with that platform they can also download the materials easily. However, students also perceived some issues within the use of Google Classroom such as the issue with the notification, the display, low control from the teacher, as well as the signal and quota. This suggests that Google classroom brings many advantages for the learning during the pandemic time but sometimes it presents some issues which need to be tackled so that the learning can run effectively.